Systemic siRNA Delivery via Peptide-Tagged Polymeric Nanoparticles, Targeting PLK1 Gene in a Mouse Xenograft Model of Colorectal Cancer - Meenakshi Malhotra; Catherine Tomaro-Duchesneau; Shyamali Saha; Satya Prakash (International Journal of Biomaterials)
Polymeric nanoparticles were developed from a series of chemical reactions using chitosan, polyethylene glycol, and a cell-targeting peptide (CP15). The nanoparticles were complexed with PLK1-siRNA. The optimal siRNA loading was achieved at an N : P ratio of 129.2 yielding a nanoparticle size of >200 nm. These nanoparticles were delivered intraperitoneally and tested for efficient delivery, cytotoxicity, and biodistribution in a mouse xenograft model of colorectal cancer. Both unmodified and modified chitosan nanoparticles showed enhanced accumulation at the tumor site. However, the modified chitosan nanoparticles showed considerably, less distribution in other organs. The relative gene expression as evaluated showed efficient delivery of PLK1-siRNA (0.5 mg/kg) with 50.7±19.5% knockdown (P=0.031) of PLK1 gene. The in vivo data reveals no systemic toxicity in the animals, when tested for systemic inflammation and liver toxicity. These results indicate a potential of using peptide-tagged nanoparticles for systemic delivery of siRNA at the targeted tumor site.